2016
DOI: 10.1097/mpa.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual and Reproductive Factors, Hormone Use, and Risk of Pancreatic Cancer

Abstract: Objectives We aimed to evaluate the relation between menstrual and reproductive factors, exogenous hormones, and risk of pancreatic cancer (PC). Methods Eleven case-control studies within the International Pancreatic Cancer Case-Control Consortium (PanC4) took part in the present study, including in total 2,838 case and 4,748 control women. Pooled estimates of odds ratios (ORs) and their 95% confidence intervals (CIs) were calculated using a two-step logistic regression model and adjusting for relevant covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In accordance with most of the current evidence we found no association between hormonal contraception use and pancreatic cancer risk [ 9 13 , 17 , 19 , 20 ]( S1 , S2 and S3 Tables). Neither was long-term use associated with risk of pancreas cancer which is in contrast to the suggestion by one previous cohort study [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with most of the current evidence we found no association between hormonal contraception use and pancreatic cancer risk [ 9 13 , 17 , 19 , 20 ]( S1 , S2 and S3 Tables). Neither was long-term use associated with risk of pancreas cancer which is in contrast to the suggestion by one previous cohort study [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our literature search revealed one previously published meta-analysis that assessed the association between pancreatic cancer risk and female hormonal and menstrual factors[ 12 ], and one pooled analysis from the international pancreatic cancer case-control consortium[ 39 ]. In contrast to our results, a previous meta-analysis found no significant associations between the risk of pancreatic cancer and OC use–pooled RR from six case-control studies and eight cohort studies was 1.09 (95%CI: 0.96-1.23)[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 27 For MHT use, controversies exist, and inverse relationships between MHT use and pancreatic cancer risk have recently been reported. 8 , 19 , 22 Furthermore, one study has identified increased risk with increasing age at menarche. 8 Likewise, higher age at first birth was identified as a risk factor for pancreatic cancer in a meta-analysis published in 2016, and a more recent cohort study supported this finding.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have assessed the relationship between pancreatic cancer risk and reproductive factors, such as age at menarche, age at menopause, menopausal status, parity, abortions, age at first birth, breastfeeding, total menstruation duration, and exogenous hormone use, have reported inconsistent results. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In 2012, a large European cohort study assessed the association between reproductive factors, hormone use, and risk of pancreatic cancer. 21 No significant association was identified.…”
Section: Introductionmentioning
confidence: 99%